HIV and HCV screening by non-infectious diseases physicians: can we improve testing and hidden infection rates? - García-Ruiz de Morales, Alejandro G.; Martínez-Sanz, Javier; Vivancos-Gallego, María J.; Sánchez-Conde, Matilde; Vélez-Díaz-Pallarés, Manuel; Romero-Hernández, Beatriz; Vázquez, María Dolores González; de Luque, Carmen María Cano; González-Sarria, Ander; Galán, Juan Carlos; Rodríguez, Francisco Gea; Moreno, Santiago; et al. (Frontiers in Public Health, 2023)
Background Missed opportunities for Human Immunodeficiency Virus (HIV) and Hepatitis C Virus (HCV) testing remain high. We aimed to ascertain the knowledge of screening guidelines and attitudes of non-infectious disease (ID) hospital physicians and assess the impact of a 1-h session on screening rates and diagnoses. Methods This interventional study consisted of a 1-h training session on HIV and HCV epidemiology and testing guidelines for non-ID physicians. Pre-and post-session questionnaires compared the knowledge of the guidelines and attitudes toward screening before and after the session. Rates of screening and diagnoses were compared in three 6 months periods: before, immediately after, and 24 months ±4 after the session. Results A total of 345 physicians from 31 departments participated in these sessions. Before the session, 19.9% (28% medical, 8% surgical) and 17.9% (30% medical, 2.7% surgical) were aware of HIV and HCV testing guidelines, respectively. The willingness to routinely test increased from 5.6 to 22%, whereas not ordering tests decreased from 34.1 to 2.4%. HIV screening rates significantly increased by 20% after the session (7.7 vs. 9.3 tests per 103 patients; p < 0.001), and the effect persisted until the long-term period. The HIV diagnosis rate increased globally (3.6 vs. 5.2 HIV diagnoses per 105 patients; p = 0.157), mainly because of medical services (4.7 vs. 7.7 per 105 patients; p = 0.082). The HCV screening rate increased significantly immediately and in the long term only in medical services (15.7 and 13.6%, respectively). The new active HCV infection rates increased immediately and declined steeply thereafter. Conclusion A short session for non-ID physicians can improve HIV/HCV screening, increase diagnosis, and contribute to disease elimination.